Women and the Holodomor Genocide: Victims, Survivors, Perpetrators: Proceedings of the Second Symposium Commemorating of the 85th Anniversary of the Holodomor-Genocide: Book review - Kis, Oksana (Український історичний журнал, 2020)
Book review